Development and Validation of HPTLC Method for Estimation of Propranolol Hydrochloride and Flunarizine Dihydrochloride in Combined Dosage Form. (9th July 2012) - Patel, Palak; Bhatt, Kashyap K.
Abstract : A simple, sensitive, and precise high-performance thin layer chromatographic method has been developed for the estimation of propranolol hydrochloride and Flunarizine dihydrochloride in combined dosage form. The method employed HPTLC aluminum plates precoated with silica gel 60F as the stationary phase while the solvent system was toluene:methanol: ethyl acetate: acetic acid (7 : 1.5 : 1.5 : 0.1 v/v/v/v). The Rf value was observed to be 0.07 ± 0.02 and 0.67 ± 0.02 for propranolol hydrochloride and flunarizine dihydrochloride. The densitometric analysis was carried out in absorbance mode at 240 nm. The method was linear in the range of 400–2400 ng/band for propranolol hydrochloride and 50–300 ng/band for flunarizine dihydrochloride. The method was validated with respected accuracy, precision and specificity. The limit of detection for Propranolol hydrochloride and flunarizine dihydrochloride were found to be 118.4 and 13.75 ng/spot, respectively. The limit of quantification for propranolol hydrochloride and flunarizine dihydrochloride was found to be 355.2 and 45.4 ng/band, respectively. The method was successfully applied to the estimation of propranolol hydrochloride and flunarizine dihydrochloride in combined dosage form.